Customers attitude toward Islamic mobile banking in Indonesia: Implementation of TAM - Alex Fahrur Riza; Muhammad Riza Hafizi (Asian Journal of Islamic Management, 2020)
Purpose: This study aims to test consumer acceptance of mobile banking Islamic banks using the Technology Acceptance Model. The concept of mobile banking is used to examine the role of banking in facilitating mobile consumer financial transactions.